Storybird: A Motivational Storytelling Website to Increase Students’ Ability In Narrative Writing - Arianti, Poppy Eki (Journal of English Teaching, Literature, and Applied Linguistics, 2018)
Writing is an essential tool for communication. Good writing allows people to communicate clearly. Among the four basic skills, writing is the most complicated one. Writing has several types and one of them is narrative. The purposes of narrative are to tell story and share information whether it is a book, thesis, journal, and an article. Unfortunately, some students do not like to write. They think that writing is so complicated and they always feel that English is horrible. Such negative attitudes are problematic in ESL/EFL writing classroom. The arising of media techonology like Storybird as internet-based CALL and an interactive storytelling website helps to boost student engagement and the students’ ability in narrative writing will increase. Meanwhile, by using Storybird, the students can study narrative writing at anywhere and anytime as long as each student has an internet connection and a laptop or netbook. The students can use it by themselves because there is a simple guide for them available in Storybird. Through Storybird, they can be autonomous learners and it is related to the Principle of Eclecticism. The aims of this article are to give a brief description about the importance and the guidelines of using Storybird in teaching and learning narrative writing. Storybird will promote literacy, enthusiasm, imagination, creativity and collaboration in learning narrative writing